Depression: A Comprehensive Documentary Analysis of its Concept, History, and Alternative Approaches - Héctor Mauricio Mazo Álvarez; Marjorie Pérez Villa; Valeria Tapias Huertas; Tatiana Carmona Ospina; María Fernanda Ossa Gaviria; Manuela Herrera Gallo (RHS Revista Humanismo y Sociedad)
This text aims to provide information about depression; a common mental disorder associated with significant psychological distress. It explores the conceptualization, historical development, symptoms, possible causes and most common treatments for depression along with an alternative perspective, approached through a qualitative paradigm and a historical-hermeneutic lens. To this end, a documentary analysis was conducted using sources from the PubMed, Dialnet, Scielo, and Scopus databases. The findings suggest that comprehensive treatment for depression typically involves medication and psychological therapy. However, additional support strategies can enhance the healing process. This includes helping individuals more accurately identify and express emotions such as sadness, guiding them in redefining the meaning of life, and encouraging a shift from feelings of helplessness and victimization in the face of the illness to a sense of responsibility for their own well-being. Such strategies may contribute to initiating a more profound and authentic recovery.